HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP KEJADIAN ANEMIA DI PUSKESMAS RAWAT INAP SIMPANG TIGA - Zalni, Rummy Islami; Yulita, Emi; Anita, Wan; Juwita, Ratna; Aprianti, Sely (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The main factor causing anemia is a lack of iron intake. Lack of consuming protein can result in delays in the transportation of substances, which can cause iron deficiency. The World Health Organization (World Health Organization 2020) states that the prevalence of pregnant women worldwide who experience anemia is 41.8%. Anemia in pregnancy can have a negative impact on maternal and fetal mortality and morbidity. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women towards the incidence of anemia at the Simpang Tiga Inpatient Health Center in 2023. This research was conducted in August. This research is a quantitative study with a cross sectional approach. The population is all pregnant women who have checked their pregnancies at the Simpang Tiga Inpatient Health Center in the last 3 months. The sampling technique is total sampling with a total sample of 59 people. The results showed a p value = 0.266 which indicated that there was no relationship between knowledge and the incidence of anemia, and a value of p = 0.906 which indicated that there was no relationship between attitude and the incidence of anemia. It is recommended that pregnant women be more active in digging up information about anemia in pregnancy so that pregnant women are healthier and avoid anemia.Keywords: Knowledge, attitude, Anemia, pregnant women